Recent advances in the study of Spanish sociophonetic perception - Chappell, Whitney (Amsterdam ; Philadelphia : John Benjamins Publishing Company, 2019)
"This book provides a cutting-edge exploration of the social meaning of phonetic variation in the Spanish-speaking world. Its 11 chapters elucidate the ways in which listeners process, perceive, and propagate phonetically motivated social meaning across monolingual and contact varieties, including the Spanish spoken in Spain (Asturias, Catalonia, and Andalusia), Ecuador, Colombia, Argentina, Chile, Mexico, and the United States. The book presents a wide variety of new and innovative research by renowned scholars, and the chapters examine issues like the influence of visual cues, bilingualism, contact, geographic mobility, and phonotactic predictability on social and linguistic perception. Additionally, the volume engages in timely discussions of intersectionality, replicability, and the future of the field. As the first unified reference on Spanish sociophonetic perception, this volume will be useful in graduate and undergraduate classrooms, in libraries, and on the bookshelf of any scholar interested in Spanish sociophonetics"--
Prelim pages -- Table of contents -- Introduction -- Spain -- Chapter 1. The role of social cues in the perception of final vowel contrasts in Asturian Spanish -- Chapter 2. Covert and overt attitudes towards Catalonian Spanish laterals and intervocalic fricatives -- Chapter 3. Dialectology meets sociophonetics -- South America -- Chapter 4. Regional identity in Highland Ecuador -- Chapter 5. Spanish and Palenquero -- Chapter 6. The role of social networks in cross-dialectal variation in the perception of the Rioplatense assibilated pre-palatal [ʃ] -- Chapter 7. The social perception of intervocalic /k/ voicing in Chilean Spanish -- North America -- Chapter 8. The sociophonetic perception of heritage Spanish speakers in the United States -- Chapter 9. Spoken word recognition and shesheo in Northwestern Mexico -- Chapter 10. The perception-production connection -- Future Directions -- Chapter 11. Of intersectionality, replicability, and holistic perspectives -- Chapter 12. Future directions for sociophonetic research in Spanish -- Index
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on December 03, 2019).
eBooks on EBSCOhost
Keywords: Spanish language -- Phonetics; Sociolinguistics -- Spanish-speaking countries; Speech perception; Speech Perception; Espagnol (Langue) -- Phonétique.; Sociolinguistique -- Hispanophonie; Perception de la parole; LANGUAGE ARTS & DISCIPLINES / Linguistics / Phonetics & Phonology; Sociolinguistics; Spanish language -- Phonetics; Speech perception; Spanish-speaking countries